STRATEGI ONLINE MARKETING BERSAMA GRAB DAN GO-BIZZ BAGI UMKM DI SURABAYA - Rika Rahayu; Maratus Zahro; Dewi Maryam (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The government has made maximum efforts and is fully committed to overcoming poverty and prospering the people through entrepreneurship development programs through training activities. The main reason why independent business training needs to be done is because Micro, Small and Medium Enterprises (MSMEs) have the potential to stabilize the economy through online marketing strategies. Training and facilitation of independent business incubation facilitation activities are carried out to increase the empowerment of MSMEs in order to increase their business or motivate them to continue their business. MSMEs in Bubutan District started to improve MSME performance with the MSME implementation method in Bubutan District, Surabaya City. The material given to MSMEs consisted of: Joint Marketing of Grab and Gojek for MSMEs in Bubutan District. The last stage of this training is monitoring and evaluation with representative results, namely, MSMEs through the Go-bizz application by emphasizing the quality of packaging and product label design, as well as culinary business ethics have implemented online marketing by registering at GRABFOOD and Go-bizz for MSME handicrafts has have unique and innovative packaging as well as food and beverage.